Clinical and serological features of patients referred through a rheumatology triage system because of positive antinuclear antibodies. - Christie Fitch-Rogalsky; Whitney Steber; Michael Mahler; Terri Lupton; Liam Martin; Susan G Barr; Dianne P Mosher; James Wick; Marvin J Fritzler (PLoS ONE, 2014)
Background The referral of patients with positive anti-nuclear antibody (ANA) tests has been criticized as an inappropriate use of medical resources. The utility of a positive ANA test in a central triage (CT) system was studied by determining the autoantibody profiles and clinical diagnoses of patients referred to rheumatologists through a CT system because of a positive ANA test. Methods Patients that met three criteria were included: (1) referred to Rheumatology CT over a three year interval; (2) reason for referral was a "positive ANA"; (3) were evaluated by a certified rheumatologist. The CT clinical database was used to obtain demographic and clinical information and a serological database was used to retrieve specific ANA and/or extractable nuclear antigen (ENA) test results. Clinical information was extracted from the consulting rheumatologist's report. Results 15,357 patients were referred through the CT system; 643 (4.1%) of these because of a positive ANA and of these 263 (40.9%) were evaluated by a certified rheumatologist. In 63/263 (24%) of ANA positive patients, the specialist provided a diagnosis of an ANA associated rheumatic disease (AARD) while 69 (26.2%) had no evidence of any disease; 102 (38.8%) had other rheumatologic diagnoses and 29 (11%) had conditions that did not meet AARD classification criteria. Of ANA positive archived sera, 15.1% were anti-DFS70 positive and 91.2% of these did not have an AARD. Conclusions This is the first study to evaluate the serological and clinical features of patients referred through a CT system because of a positive ANA. The spectrum of autoantibody specificities was wide with anti-Ro52/TRIM21 being the most common autoantibody detected. Approximately 15% of referrals had only antibodies to DFS70, the vast majority of which did not have clinical evidence for an AARD. These findings provide insight into the utility of autoantibody testing in a CT system.